(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study aimed to find the hidden ideological approaches used by the newspaper editors in the portrayal of their cartoons in the respective newspapers. The target of this research was to achieve a broad spectrum comparison of semiotics as depicted in international newspapers as Dawn based in Pakistan and The Economist based in Britain. The objectives of the research were achieved by dividing the study into two parts. At first, the written parts of the cartoons were analyzed, and secondly, the semiotics was analyzed. An integrated framework of analysis was used and the researcher blended the CDA model by Norman Fairclough and the semiological framework of Roland Barthes. The study revealed that Dawn presented the domestic problems of the health care system. Further Dawn presented the severe attacks of Covid-19 and locusts and the drastic effects of locusts on the agriculture-based economy. The Economist presented an American cultural disorder of racism that has been part of its earlier history. The Economist also highlighted the precarious state of Brazil and the inefficiency of the government to tackle the spread of Covid-19. It was concluded that the semiotics presented in the newspapers portrayed the situation related to Covid-19 and its long-lasting effects have been discussed in the context of culture and social practice. A comparison of semiotics was presented at the end of the study.